AB1461-HPR Cognitive testing of physical activity questions in a population of patients with rheumatoid arthritis: A validation study. (23rd January 2014) - Thomsen, T.; Loeppenthin, K.; Esbensen, B.A.; Midtgaard, J.
Abstract : Background: Research has documented that physical activity (PA) may lead to health benefits for both the general population as for individuals with rheumatoid arthritis (RA) 1 . Such studies often use self-administered questionnaires to measure PA. A majority of the included instruments has been validated on healthy but are also used in subgroups such as individuals with chronic disease, based on the assumption that all respondents perceive questions about PA in the same way. There is a lack of studies testing the understanding of PA questions in patients with chronic diseases. Cognitive interviewing has been proved to be a reliable method to test how a homogeneous group perceives survey questions. Objectives: we aimed to test the content and face validity of selected instruments assessing self-reported PA in a population of RA patients using cognitive interviews. This was done prior to a cross-sectional study focusing on PA in RA patients. Methods: In total, 41 RA patients aged 25-73 years, affiliated to a rheumatology outpatient clinic, participated. Each patient completed questions about PA, including Physical Activity Scale (PAS) 2, in a face-to-face semi-structured interview, using the "think aloud" method in which the patient expressed immediate thoughts aloud while answering the questions. When necessary, the interviewer probed the respondent verbally to derive more information. Reports were made from the interviews. Subsequently, data were coded according to a three-stage model 3 : 1) Understanding the intent of the question 2) Performing the primary task (mental processes in determining the answer) and 3) Response formatting (producing a response that incorporates judgement elements). Results: Most difficulties occurred in performing the primary task. Regarding questions in PAS patients also had difficulties in formatting the response, including reporting the same PA twice or thrice. A substantial problem was fitting activities within the scope of a question due to difficulties in determining the intensity and duration of the activity and personal interpretation of PA examples given in the questions. The problems were further compounded by wide variation in disease activity and general variation in weather and lifestyle. Conclusions: The results indicate a risk for report errors when patients do self-reports of PA. However, we conclude, that most of the problems are not considered specified to RA patients. Consequently, we saw no need for constructing physical activity questions for this population especially in the cross-sectional study. Cognitive interviewing has shown to be an adequate method for undertaking content and face validity of a questionnaire and is recommendable performing prior to any questionnaire surveys. References: Hurkmans E, van der Giesen FJ, Vliet Vlieland TP et al. Dynamic exercise program (aerobic capacity and/or muscle strength training) in patients with rheumatoid arthritis. Cochrane Database Syst Rev 2009; 7 (4): CD006853. Aadahl M, Jorgensen T. Validation of a new self-report instrument for measuring physical activity. Med Sci Sports Exerc 2003 Jul; 35 (7):1196-202. Willis GB. Cognitive Interviewing. A Tool for improving questionnaire design. Sage Publications, California 2005. Disclosure of Interest: None Declared